Interaction of mental accounting, financial self-efficacy, and financial attitude on financial behavior - Dwi Radianto, Wirawan Endro; Pramudita, Nieke Ayu (Enrichment : Journal of Management, 2024)
The purpose of this study is to investigate how mental accounting, financial attitude, financial knowledge, and financial self-efficacy affect the financial behavior of university students that engaged in business startups. A total of 400 questionnaires were collected from startup business owners, predominantly aged under 25 and with less than 3 years of business experience. Hypotheses were tested using SMART-PLS. The results indicate that financial attitude and financial self-efficacy have an impact on financial behavior, while mental accounting influences financial self-efficacy and financial attitude, and financial behavior. Furthermore, financial knowledge influences financial attitude, although it does not directly affect financial attitude and mental accounting